2020
DOI: 10.3390/atmos11020188
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Intense Rainfall Days in Southern West Africa and Associated Atmospheric Circulation

Abstract: Daily rainfall in southern West Africa (4-8 • N, 7 • W-3 • E) is analyzed with the aim of documenting the intense rainfall events which occur in coastal Ivory Coast, Ghana, Togo, and Benin. The daily 99th percentile (P99) shows that the coastline experiences higher intensity rainfall than inland areas. Using Tropical Rainfall Measuring Mission (TRMM) rainfall data for 1998-2014, a novel way of classifying the intense events is proposed. We consider their space-time structure over a window of 8 • latitude-longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
(86 reference statements)
1
3
0
1
Order By: Relevance
“…Moreover, the identified CPs of the subseasonal classification, associated with intense rainfall amounts (CP4 and CP6), are related to westward propagating wind systems at 700 hPa. This is in agreement with the study by Camberlin et al (2020). Thus, the classification can generate relatively reliable CP patterns for the study region of interest.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, the identified CPs of the subseasonal classification, associated with intense rainfall amounts (CP4 and CP6), are related to westward propagating wind systems at 700 hPa. This is in agreement with the study by Camberlin et al (2020). Thus, the classification can generate relatively reliable CP patterns for the study region of interest.…”
Section: Discussionsupporting
confidence: 94%
“… Note : a, Moron et al (2008a); b, Laux (2009); c, Guèye et al (2011); d, Moron et al (2018); e, Camberlin et al (2020). …”
Section: Methodsunclassified
See 1 more Smart Citation
“…As cluster 4 shows, most of the rainfall in this zone occurs in the boreal summer, with a peak in August (Nicholson et al, 2018). Cluster 2 and 3 have also featured prominently in previous literature as the other three regions described above, with the terms' Guinean' and 'Sudanian' used to describe them, respectively (Akumaga & Tarhule, 2018, Camberlin et al, 2020, possibly due to the vegetation class in these regions.…”
Section: -Rainfall Regionalizationmentioning
confidence: 68%
“…In North Benin, Lawin [53] found an average duration per event of about 5 h. In his PhD thesis, Mathon [6] showed that the convective systems south of 9 • N are less organized and, over the Côte d'Ivoire, these systems also have short lifetimes. Maranan et al [59] and Camberlin et al [60] also noted these characteristics of less-organized, smaller, and more short-lived systems along the West African coast. However, beyond meteorological considerations, the difference in the size of the three rain gauge networks could also partly explain the differences observed in the duration of rainfall events.…”
Section: Discussionmentioning
confidence: 89%